Prediction of individual differences in risky behavior in young adults via variations in local brain structure - Nasiriavanaki, Zahra; ArianNik, Mohsen; Abbassian, Abdolhosein; Mahmoudi, Elham; Roufigari, Neda; Shahzadi, Sohrab; Nasiriavanaki, Mohammadreza; Bahrami, Bahador (Frontiers in Neuroscience, 2015)
In recent years the problem of how inter-individual differences play a role in risk-taking behaviour has become a much debated issue. We investigated this problem based on the well-known balloon analogue risk task (BART) in which participants inflate a virtual balloon opting for a higher score in the face of a riskier chance of the balloon explosion. In this study, based on a structural Voxel Based Morphometry (VBM) technique we demonstrate a significant positive correlation between BART score and size of the grey matter volume in the anterior insula in riskier subjects. Although the anterior insula is among the candidate brain areas that were involved in the risk taking behaviour in fMRI studies, here based on our structural data it is the sole area with a significant structural variation among different subjects. Also a seemingly conflicting finding is discussed where the anterior insula is shown to be more active in risk aversive subjects.